Speeches presented...during the period July 2005 to December 2005 - Bourne, Compton (CDB St. MichaelBB, 2006)
Looks at the financing of higher education in the Caribbean. Highlights the sharing of the benefits of economic integration and suggests the creation of a sustainable framework for the monitoring of the achievement of the Millennium Development Goals. Deals with the national planning by small states in the face of declining overseas development assistance. Suggests broad outlines for the adjustment and change that is necessary for economies of Caribbean countries.